Innovative Formulation and Evaluation of Betahistine Floating Tablets for Vertigo Management: Pharmaceutical sciences- Pharmaceutics - Kumar, Pavan; PG, Subhash; Abdul Ahad, Hindustan; Dhamala, Pawan; D, Suprith; Sequeira, Chrishmitha (International Journal of Life Science and Pharma Research, 2024)
Floating tablets are designed to improve the effectiveness and consistency of medication delivery. These specializedoral drug delivery systems are engineered to float on the gastric fluid in the stomach for an extended period, ensuring prolongedgastric retention that leads to a slow and controlled drug release, ultimately enhancing its bioavailability and therapeutic efficacy.Meniere’s disease comprises recurrent spontaneous rotatory vertigo spells that patients describe as a spinning or whirling feelingand sensorineural hearing loss (SNHL) accompanied by recruitment and tinnitus. This study aimed to create buoyant tabletscontaining Betahistine (BTH) for treating Meniere’s disease, designed to float in fluids and discharge the drug gradually. Theapproach involved the utilization of HPMC K4M 100 and Chitosan in combination as agents for swelling. Gas generation wasfacilitated by sodium bicarbonate and citric acid, while lactose was incorporated as a bulking agent. Tablets were fabricated usingthe direct compression technique and subjected to various assessments, including thickness, hardness, weight consistency,friability, BTH content, swelling capacity, buoyancy, and BTH release patterns. Notably, FTIR analyses indicated the absence ofsignificant interactions between the BTH and its constituents. This comprehensive strategy underscores the potential of thesetablets as a reliable and enduring treatment choice for Meniere’s disease. Among nine formulations, F5 displayed the least BTHdischarge (73.47±1.27% over 12 h), while F2 demonstrated the highest discharge (85.92±2.36% over 12 h). These findingshighlight formulation F5’s potential for controlled BTH discharge, which could be beneficial in managing Meniere’s diseasesymptoms. This thorough investigation contributes to optimizing the formulation to treat Meniere’s disease with buoyant tabletsincorporating Betahistine efficiently.